Dampak Implementasi Merdeka Belajar Kampus Merdeka (MBKM) Pada Dosen, Mahasiswa, Dan Tenaga Kependidikan Di Universitas Katolik Widya Mandala Surabaya - Ignasius Radix Astadi Praptono Jati; Hendra Wijaya; Kristina Pae (Eduka : Jurnal Pendidikan, Hukum, dan Bisnis, 2022)
The purpose of this study was to determine the impact of MBKM implementation on lecturers, students, and education staff at Widya Mandala Surabaya Catholic University. This research is a descriptive research category and the approach chosen is formative evaluation. Data collection was carried out using a questionnaire. The results of this study are that; 1) lecturers, students, and education staff have known and understood the existence of the MBKM program; 2) before the MBKM program was established, all study programs had similar programs; 3) lecturers, students, and education staff are interested in participating in MBKM programs; 4) lecturers, education staff and students recommend the MBKM program to be followed by all students taking into account the challenges that must be overcome, namely adjusting the MBKM curriculum, improving existing information systems, and formalizing collaboration with partners.Keywords: MBKM; effect; evaluation